2022
DOI: 10.3390/coatings12040533
|View full text |Cite
|
Sign up to set email alerts
|

Gloss Level of HDF Finished with Different Numbers of Layers and Hardened with UV Hg-Ga Lamps of Selected Power

Abstract: A key feature of varnish coatings on furniture surfaces is their optical properties, which often determine customers’ purchase choices. Furniture may be produced using various boards, which are much cheaper than wood-based materials. For their finishing, among others, UV-cured varnish products are used. The aim of this study was to determine the effect of different types of HDF boards, the amount of basecoat and topcoat applied, the number of layers, and the different lamp powers used for hardening on the glos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The interactions between the spread rates of varnish and the mercury lamp power were Based on these, the author concluded that a thicker coating layer increases the coating resistance. This is consistent with the information provided on quality improvement when more topcoat is applied [54,55]. However, the same principle was not used with the priming varnish.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The interactions between the spread rates of varnish and the mercury lamp power were Based on these, the author concluded that a thicker coating layer increases the coating resistance. This is consistent with the information provided on quality improvement when more topcoat is applied [54,55]. However, the same principle was not used with the priming varnish.…”
supporting
confidence: 83%
“…In the literature, it is also possible to find publications on the increase in gloss with the application of successive varnish coats [45]. Lower gloss was observed with higher topcoat thickness when finishing using conventional UV lamps [55]. This may be due to differences in the composition of varnishes cured by mercury lamps and LED lamps.…”
Section: Gloss Levelmentioning
confidence: 99%
“…It is attributed to the fact that C 2 and C 3 contain more photoinitiator 819DW than C 1 , as a result, more photoinitiators lead to denser wrinkles 44 and higher matting efficiency. 8,45 The gloss value of F 1 is much lower than those of F 2 and F 3 with the incident angle of 85°. The reason is that the height and spacing of wrinkles in F 1 surface are higher than those in F 2 and F 3 (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The present study is a continuation of a gloss and color study conducted on the same variants [ 41 ]. For this study, 48 variants were selected.…”
Section: Methodsmentioning
confidence: 99%